2010
DOI: 10.1103/physrevc.82.054306
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal extension of the dispersive optical model to describe data below the Fermi energy

Abstract: Present applications of the dispersive-optical-model analysis are restricted by the use of a local but energy-dependent version of the generalized Hartree-Fock potential. This restriction is lifted by the introduction of a corresponding nonlocal potential without explicit energy dependence. Such a strategy allows for a complete determination of the nucleon propagator below the Fermi energy with access to the expectation value of one-body operators (like the charge density), the one-body density matrix with ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
98
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(111 citation statements)
references
References 55 publications
12
98
1
Order By: Relevance
“…F and employ the subtracted form of the dispersion relation calculated at this energy [5,8] Re Σ ℓj (r, r…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…F and employ the subtracted form of the dispersion relation calculated at this energy [5,8] Re Σ ℓj (r, r…”
mentioning
confidence: 99%
“…The solution of the Dyson equation below the Fermi energy was introduced in Ref. [8]. The scattering wave functions are generated with the iterative procedure outlined in Ref.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Because the local version of the DOM still contains an energy-dependence related to non-locality of the real part, it distorts the normalization of the spectral strength and requires a correction for the proper normalization of spectroscopic factors. A non-local Hartree-Fock-like and energy-independent potential was introduced in [22] to avoid this issue. While this step allows the interpretation of the optical potential as representing the nucleon self-energy, it was also shown that observables like the nuclear charge density cannot be described in detail.…”
Section: Introductionmentioning
confidence: 99%